Pendidikan Multikultural di Lembaga Pendidikan Islam (Konsep dan Implementasi di Madrasah Ibtidaiyah Al-Ichsan Surabaya) - Dewi Ixfina, Ficky; Syamsudin, Syamsudin; Lailatul Fitriani, Siti (AL-WIJDÃN Journal of Islamic Education Studies, 2022)
Indonesia is a diverse nation with various ethnicities, languages, traditions, and social classes, even in the religious aspect. The fact is that Indonesians have problems figuring out how to manage multiculturalism to minimize conflict caused by the term "difference". One of the strategic plans to instill multicultural values is to implement them through an educational process that teaches multicultural and human rights. The purpose of this research is to describe multicultural education in Islamic institutions. This research uses a descriptive qualitative method, which is located at Madrasah Ibtidaiyah Al-Ichsan Surabaya, collecting data through observation, interviews, and documentation. Data analysis in this research is from data collection and conclusions. The result of this research indicates that there is awareness of the existence of multicultural education, a curriculum with a multicultural perspective, and a madrasa culture to appreciate differences. Multicultural education is implemented in the classroom and through outdoor education with various activities that emphasize teamwork. The impact of multicultural education on students is the realization of students' daily habits that show multicultural appreciation, live in harmony, and minimize various conflicts between students.   Keywords: Education, Multicultural, Islamic Educational Institutions